High‐Performance Small‐Amount Fe2O3‐Doped (K, Na)NbO3‐Based Lead‐Free Piezoceramics with Irregular Phase Evolution. Issue 7 (26th March 2016) - Guo, Jinming; Xu, Fang; Shang, Xunzhong; Lu, Yinmei; Li, Pai; Zhou, Taosheng; Zhang, Zaoli; He, Yunbin
Abstract : [(K0.43 Na0.57 )0.94 Li0.06 ][(Nb0.94 Sb0.06 )0.95 Ta0.05 ]O3 + x mol% Fe2 O3 (KNLNST + x Fe, x = 0~0.60) lead‐free piezoelectric ceramics were prepared by conventional solid‐state reaction processing. The effects of small‐amount Fe2 O3 doping on the microstructure and electrical properties of the KNLNST ceramics were systematically investigated. With increasing Fe 3+ content, the orthorhombic‐tetragonal polymorphic phase transition temperature ( T O‐T ) of KNLNST + x Fe ceramics presented an obvious "V" type variation trend, and T O‐T was successfully shifted to near room temperature without changing T C ( T C = 315°C) via doping Fe2 O3 around 0.25 mol%. Electrical properties were significantly enhanced due to the coexistence of both orthorhombic and tetragonal ferroelectric phases at room temperature. The ceramics doped with 0.20 mol% Fe2 O3 possessed optimal piezoelectric and dielectric properties of d 33 = 306 pC/N, k p = 47.0%, ε 33 T / ε 0 = 1483 and tan δ = 0.023. It was revealed that the strong internal stress in the KNLNST + x Fe ceramics with higher Fe 3+ contents ( x = 0.40, 0.60) stabilized the orthorhombic phase, leading to the irregular "V" type rather than the usually observed monotonic phase transition with composition change in the ceramics.